ROMANIA DURING CEAUSESCU'S DICTATORSHIP: FIRST PERIOD IN POWER (1965– 1971) - Dan Vătăman (Romanian Journal of Historical Studies)
The political regime of Nicolae Ceausescu had at least three distinct stages, each of these being characterized by important developments both in the internal political life and in Romania's foreign relations. The purpose of this study is to deepen the Ceausescu's first period in power (1965– 1971), stage characterized, on the one hand, by a relative democratization of society and, on the other hand, the strengthening of his personal power through the assumption of important functions in the Party and State leadership along with the continuation of the political line of independence from Moscow. Thus, research is focused on works of the Ninth Congress of the Romanian Communist Party which gave "the historical start of the new times" and also is stressed the Ceausescu's public condemnation of the Warsaw Pact troops intervention in Czechoslovakia, a courageous act which gained him and our country worldwide respect. Also, it was analyzed the Constitution of Socialist Republic of Romania from 1965 (the document that formed the legal basis for the dictatorship of Nicolae Ceausescu) and finally I focused on the end of the relative democratization period and the consolidation of Ceausescu’s personality cult